Perturbation Training in Young Female Basketball Players: A Randomized Controlled Trial - Haklı, Özge; Dincer, Sensu; Sahinkaya, Türker; Metin, Gokhan (International Journal of Sports Medicine, 2025)
Perturbation training is commonly applied; however, its effects on the peroneal muscle remain underexplored in the female basketball player population. This study aimed to investigate the effects of perturbation-based neuromuscular training (PNT) on dynamic balance, peroneal muscle strength, endurance, and functional performance in young female basketball players. A randomized controlled trial was conducted with forty young female basketball players. The players were assigned to either a perturbation-based neuromuscular training group (PG) (n=20) or a control group (CG) (n=20) by simple random allocation. PG received an 8-week neuromuscular training program (two sessions/wk) in addition to routine basketball training, while CG attended routine training only. Dynamic balance, peroneal muscle eccentric strength, endurance, vertical jump (VJ), and side hop (SH) tests were evaluated. Dynamic balance was evaluated with the Y balance test, and peroneal muscle eccentric strength and endurance were evaluated with the Cybex dynamometer. PG demonstrated significant improvements in dynamic balance (p=0.000), VJ (p=0.0049), and SH performance (p=0.010) after the training program, analyzed with analysis of variance. Peroneal eccentric strength significantly increased in PG (p=0.001 right, p=0.020 left). Both groups showed improvements in peroneal muscle endurance parameters; however, the PG group improved significantly (p=0.004 right, p=0.025 left). An 8-week PNT significantly enhances dynamic balance, eccentric eversion strength, and jump performance while contributing to reduced peroneal muscular fatigue in young female basketball players.
Keywords: neuromuscular training; peroneal strength; peroneal muscular fatigue